Single-injecting, bioinspired nanocomposite hydrogel that can recruit host immune cells in situ to elicit potent and long-lasting humoral immune responses. (September 2019) - Korupalli, Chiranjeevi; Pan, Wen-Yu; Yeh, Ching-Yen; Chen, Po-Ming; Mi, Fwu-Long; Tsai, Hung-Wen; Chang, Yen; Wei, Hao-Ji; Sung, Hsing-Wen
Abstract: Vaccination is an effective medical intervention for preventing disease. However, without an adjuvant, most subunit vaccines are poorly immunogenic. This work develops a bioinspired nanocomposite hyaluronic acid hydrogel system that incorporates N -trimethyl chitosan nanoparticles (TMC/NPs) that carry a model subunit vaccine ovalbumin (OVA) that can elicit a potent and prolonged antigen-specific humoral response. Experimental results indicate that the nanocomposite hydrogel system (NPs-Gel) can retain a large proportion of its TMC/NPs that are bonded by covalent/electrostatic interactions and extend the release of the encapsulated OVA, enabling their localization at the site of hydrogel injection. The positively charged TMC/NPs can be effectively internalized by dendritic cells, significantly augmenting their maturation, suggesting that TMC can function as an adjuvant-based OVA delivery system. Upon subcutaneous implantation in mice, the NPs-Gel acts as an in situ depot that recruits and concentrates immune cells. The TMC/NPs that do not have any specific interactions with the hydrogel network are released rapidly and internalized by the neighboring immune cells, providing a priming dose, while those retained inside the NPs-Gel are ingested by the recruited and concentrated immune cells over time, acting as a booster dose, eliciting high titers of OVA-specific antibody responses. These experimental results suggest particulate vaccines that are integrated in such a bioinspired hydrogel system may be used as single-injection prime-boost vaccines, enabling effective and persistent humoral immune responses.